Transforming Physics Education: Harnessing the Potential of Concept Mapping Across Cognitive Domains (Pragyaratna प्रज्ञारत्न, 2024)
This study aimed to investigate how concept mapping affects student performance in physics education across different cognitive areas. It concerns a study conducted at Tribhuvan University-affiliated education campuses in Kathmandu and Bhaktapur districts, employing a quasi-experimental pre-test and post-test design. The investigation delves into the efficacy of concept mapping as an instructional tool to enhance student learning outcomes in physics education. The research design included a Control group with 70 participants and an Experimental group with 95 participants. The study showcased superior posttest performance in the Experimental group compared to the Control group across Knowledge, Understanding, Application, and Higher levels of cognitive domains. These findings underscore the effectiveness of Concept Mapping in enhancing student performance, positioning it as a promising educational strategy in physics instruction. The study employed the Kuder-Richardson 21 test to validate the instrument's reliability (coefficient of 0.78) and utilized SPSS version 20 for data analysis. Concept Mapping proves effective in enhancing physics education, demonstrating notable improvement in student achievement across various cognitive domains. Finding of the study revealed that Concept Mapping effectively improved posttest outcomes, emphasizing its beneficial influence on students' understanding and utilization of physics principles.